Ability to create goal opportunities: influence of playing either at home or away, dimensions of the field and number of passes per attack cycle in an under-19 elite football team ability - José Alberto Martínez Sánchez; Antonio Manuel Solana Sánchez; Francisco Javier Núñez Sánchez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study was to analyse how, when playing either at home or away, the dimensions of the field (length and width), and number of passes per attack cycle influenced the ability to create goal opportunities for an under-19 football team. The total number of cycles in which a goal-scoring opportunity occurred, differentiated by the starting zone of the cycle, the number of contacts necessary to develop the attack cycle, and the effective match time, were analyzed in each different contexts. In games played at home, records of variables analyzed are greater than in games played away. The use of a smaller number of contacts in attacks initiated in the opposite field, and a greater number of contacts in attacks initiated in one's own field, favors the creation of goal opportunities. Playing fields with dimensions similar to the most familiar one favor a greater number of contacts with the ball and increased effective time of play. The efficiency of a team’s style of play in creating goal opportunities changes depending on whether they play at home or away, the size of the field, and the number of passes per attack cycle.